Three phase boost rectifier design - Saher, Rohaizan (2012)
An electric power can be converted from one form to another form by using power electronics devices. The function of power electronics circuits by using semiconductor devices as switch is modifying or controlling a voltage. The goal of power electronics circuits are to convert electrical energy from one form to another, from source to load with highest efficiency, high availability and high reliability with the lowest cost, smallest size and weight. The term rectification refers to the power circuit whose function is to alter the ac characteristic of the line electric power to produce a “rectified”ac power at the load side that contain the dc value In this project, a study has done for the two types of rectifier topology of alternating current to direct current voltage of a three-phase boost rectifier with pulse width modulation (PWM) and a threephase boost rectifier with active power filter (APF). Power factor, shape distortion and